Fish, fishing and community in North Korea and neighbours (2020)
Romanisation is one of the greatest challenges when it comes to coherent writing and scholarship focused on the Korean peninsula. There are currently at least four separate romanization strategies for converting Korean Hangeul (한글) or Chosŏn'gŭl (조선) script into an English language context. Both Koreas, of course, use entirely different approaches and have changed these approaches over time. North Korean romanisation style refers to Pyongyang and Kim Il Sung, whereas South Korea’s current Revised Romanisation strategy (in its 2008 form), refers to Pyeongyang and Kim Il-song. There is an extraordinary amount of politics and ideology in the use of these different strategies and it is an issue for all scholars when quoting from text produced in both current Korean nations to either choose one over the other, or to Romanise according to the source of the quotation, place name, person or text. This book, therefore, adopts a strategy as far as possible of objective multiplicity. This, of course, inevitably breaks all the usual patterns of uniformity in documents and is contested as a technique, certainly not problematic, nor free of ideology or presumption. In the case of historical Korean names, places, concepts and nations, the book uses the McCune Reischauer romanization strategy created in 1937 by George McCune of the University of California, Berkeley and Edwin Reischauer of Harvard University. While McCune essentially crystallises some of political imperialism, academic elitism and Orientalism of the twentieth century and complicates written Korean with judicious and at times excessive use of diacritic marks, it is a comprehensive system of romanisation that avoids the politics and ideology of the present. When using Korean names, places and concepts in North Korea, the book uses the North Korean romanisation strategy. When using Korean names, places and concepts in South Korea the book uses the Revised Romanisation strategy from 2008. On occasion when a term or name is important to both, on the first instance in a chapter the book includes both romanisations. Following the tradition instigated by Prof. David Mason the book uses the spelling sanshin, when it comes to traditions of Korean mountain deities and sanshingak when it comes to their places of veneration.